AB0780 Frequency and characteristics of cancer associated myositis in a cohort of 20 patients with anti-jo-1 positive myositis. (23rd January 2014) - Meyer, A.; Theulin, A.; Chatelus, E.; Sordet, C.; Javier, R.-M.; Lannes, B.; Geny, B.; Gottenberg, J.-E.; Sibilia, J.
Abstract : Background: Anti-Jo-1 has been negatively associated with cancer. Accordingly, only few reports described the co-existence of anti-Jo-1 positive myositis and malignancy. Despite the apparent rarity of this association, Jo-1 has been shown to be over express by a variety of tumors and it has been proposed that this could lead in some cases to tolerance breakdown. Methods: We retrospectively determined the frequency of cancer-associated myositis (CM) in a cohort of 20 anti-Jo-1 positive myositis diagnosed between January 1st 1994 and January 1st 2011 at the Strasbourg University Hospital were reviewed. CM was defined as cancer occurring within the 3 years of myositis diagnosis and, if the cancer is cured, the cure of the myositis as well (as per the modified Bohan and Peter classification of Troyanov et al. (6). To better address the question of a fortuitous or a paraneoplasic link between cancer and anti-Jo-1 positive myositis, we assessed the expression of Jo-1 in available tumor and healthy tissues by immunohistochemistery with monoclonal anti-Jo-1 antibody (Abcam). Results: A CM was diagnosed in one patient (5%). A 55 year old woman, smoker, presented a antisynthetase syndrome complicated with myocardial injury. After 3 solumedrol bolus, oral corticosteroids (1.5 mg/kg/day), mycophenolate mofetil (2 g/d) infusion of rituximab (1g) and an infusion of immunoglobulins (2 g/kg), evolution was only mildly favorable. Concomitantly, a nodule of the right breast was found, the biopsy revealed an infiltrating ductal carcinoma. There was no other location. Right mastectomy was performed, followed by chemotherapy, radiotherapy and hormone therapy. Within 4 weeks following surgery, the symptoms disappeared dramatically. 6 months after the mastectomy all immunomodulatory therapy, including corticosteroids, was stopped. 1 year after stopping treatment, myositis was still in remission. Immunohistochemical study of the specimen showed an overexpression of Jo-1 in the cytoplasm of tumor cells compared to normal cells. Conclusions: It cannot be ruled out that chemotherapy had an immunomodulatory effect by itself on myositis. anti-Jo-1 myositis were characterised by a chronic course and all patients relapsed within the year following the steroid taper to 5mg or less (7). One year and half after the stop of cortiocosteroids therapy, our patient myositis was still in remission. Moreover, Jo-1 antibodies disappeared. All together, these data suggest that anti-Jo-1 positive myositis was an authentic paraneoplasic syndrome in this patient. For the first time, we studied expression of Jo-1 antigen in a patient with anti-Jo-1 positive CM. Immunohistochemistery assays showed that Jo-1 was over expressed in tumor cells. This result corroborates the hypothesis of a triggering role of the tumour on autoimmune process. The positivity of Jo-1 antibodies may not be an exclusion criterion for the diagnosis of cancer-associated myositis. A thorough age-appropriate malignancy work up may be indicated in all patients with a new diagnosis of myositis, despite the presence of anti-Jo-1 antibodies. Disclosure of Interest: None Declared